Evaluating the impact of amino acid spray on melon (Cucumis melo L.) growth under hydroponic conditions at Polije SGH - Kusparwanti, Tri Rini; Pertami, Rindha Rentina Darah; Ermawati, Netty; Suwardi, Suwardi; Salim, Abdurrahman (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Melon (Cucumis melo L.) is one of the horticultural plants of the fruit type which is included in the gourd tribe or Cucurbitaceae family. The problem of melon cultivation in the field is that it requires intensive maintenance, is susceptible to pests and diseases, uses less efficient nutrients, is sensitive to weeds, and has less controlled growth. The above problems can be overcome by hydroponic techniques. In hydroponic techniques, environmental resources are easier to control and the results obtained are more satisfying compared to conventional cultivation, especially in open fields. Amino acids are proteins that have been broken down through the metabolic process into small molecules. In addition to humans, plants also need amino acids to increase overall yields and quality. Methods: This study aims to determine the effect of providing the best Amino Plant concentration for the growth and production of melon plants. This study was conducted in June - October 2022 at the Smart Green House (SGH) of Jember State Polytechnic. The experimental design used was a Completely Randomized Design (CRD) consisting of one factor, namely the concentration of Amino Acid with 3 levels, namely P1 (4 mg/L), P2 (8 mg/L), and P3 (12 mg/L). Results: The results of the study showed that the administration of Amino Acids at a dose of 2 g/L gave results that were not significantly different (ns) in all parameters and showed that there was no effective concentration for melon growth and production in all parameters.Conclusion: Based on the results of this research, it is recommended to carry out further research by applying Amino Plant according to the guidelines on the packaging. It is necessary to calibrate the drip irrigation or fertigation system so that the nutrient flow is uniform.